2004
DOI: 10.1038/sj.hdy.6800476
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific hybridization among Hieracium species in New Zealand: evidence from flow cytometry

Abstract: Hieracium pilosella (Asteraceae) was accidentally introduced to New Zealand about 100 years ago. Since then it has become an aggressive weed, and an unexpected degree of genetic and genome size variation has been detected; features that might result from interspecies hybridization. We investigated the possibility that H. pilosella has hybridized with related taxa. Of the four other subgenus Pilosella species introduced to New Zealand, H. praealtum is the most abundant and, on morphological and distributional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…For example, in a secondary distribution area, the formation of new Hieracium subgen. Pilosella hybrids has been recorded (Lepage 1967;Houliston and Chapman 2004;Morgan-Richards et al 2004;Trewick et al 2004). The presence of hybridization, even in apomicts, most likely facilitated the success of a number of highly invasive biotypes (Chapman et al 2003;Wilson et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…For example, in a secondary distribution area, the formation of new Hieracium subgen. Pilosella hybrids has been recorded (Lepage 1967;Houliston and Chapman 2004;Morgan-Richards et al 2004;Trewick et al 2004). The presence of hybridization, even in apomicts, most likely facilitated the success of a number of highly invasive biotypes (Chapman et al 2003;Wilson et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, among the herbarium specimens we received from Tierra del Fuego, H. floribundum (a hybridogenous species originated from H. caespitosum and H. lactucella) was also present. All of these species are known to hybridise with H. pilosella in Europe (Sell and West 1976), and at least some of them do so in New Zealand (Morgan Richards et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Pilosella are known as easily hybridising, forming both stabilised hybrids (hybridogenous species) and hybrid swarms, even between different ploidy levels (e.g., Fehrer et al 2007;Sell and West 1976). Efficient hybridisation results in the formation of new forms (either sexual or facultatively apomictic) and increases the evolutionary potential of these species (e.g., Houliston and Chapman 2001;Morgan-Richards et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Previously, FCM was used to detect interspecific hybrids obtained from reciprocal crosses between B. napus and B. rapa, as well as B. napus and B. juncea (Sabharwal and Doležel 1993). FCM was also useful for the very early detection of interspecific hybrids within the genera of Lilium (van Tuyl and Boon 1996), Centaurium (Banjanac et al 2014) and Hieracium (Morgan- Richards et al 2004). In our study, the FCM of young, fully expanded leaves revealed that all of the Brassica genotypes were characterised by high degrees of endoreplication.…”
Section: Discussionmentioning
confidence: 99%